1997
DOI: 10.1021/jp9640538
|View full text |Cite
|
Sign up to set email alerts
|

EXAFS Characterization of Rh−Pt Metal Clusters Supported on NaY Zeolite

Abstract: The size and shape of monometallic Rh and Pt and bimetallic Rh−Pt clusters on zeolite NaY were determined by EXAFS. In the monometallic as well as in the bimetallic samples, the first coordination numbers were independent of the metal loading (1.5−4.8 wt % for Pt and 0.8−2.5 wt % for Rh in monometallic samples, and 0.8−2.4 wt % for Pt and 0.4−1.2 wt % for Rh in the bimetallic samples). All first coordination numbers were around 7, demonstrating that all monometallic and bimetallic particles have similar dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 49 publications
1
21
1
Order By: Relevance
“…In contrast with bimetallic PtTM surfaces, which have been widely studied, for example, see refs, our atomistic understanding of bimetallic PtTM nanoclusters is still far from satisfactory because of the limited number of studies compared with surface alloys, for example, PtFe, PtCo, , PtNi, PtCu, PtZn, ,, PtMo, PtRu, PtRh, ,, PtPd, PtAg, ,, and PtAu, ,,, which can be explained by the following reasons. Experimental studies have found difficulties to identify the structural models at different environmental conditions because of the lack of long-range symmetry, whereas theoretical techniques have to explore a large number of local minimum configurations, in particular, for binary systems, , where a large number of configurations with different chemical distributions have similar total energies and it is a challenge for global optimization algorithms. , …”
Section: Introductionmentioning
confidence: 99%
“…In contrast with bimetallic PtTM surfaces, which have been widely studied, for example, see refs, our atomistic understanding of bimetallic PtTM nanoclusters is still far from satisfactory because of the limited number of studies compared with surface alloys, for example, PtFe, PtCo, , PtNi, PtCu, PtZn, ,, PtMo, PtRu, PtRh, ,, PtPd, PtAg, ,, and PtAu, ,,, which can be explained by the following reasons. Experimental studies have found difficulties to identify the structural models at different environmental conditions because of the lack of long-range symmetry, whereas theoretical techniques have to explore a large number of local minimum configurations, in particular, for binary systems, , where a large number of configurations with different chemical distributions have similar total energies and it is a challenge for global optimization algorithms. , …”
Section: Introductionmentioning
confidence: 99%
“…17 Compared to monocomponent Pt NPs, platinumbased nanostructures are very important due to their superior properties such as catalytic 15 and electrocatalytic properties 19,20 and also to reduce Pt usage in industrial applications because of the high cost of Pt. There are many experimental studies of platinum-based nanoalloys consisting of Pt−Fe, 21 Pt−Co, 22,23 Pt−Ni, 24,25 Pt−Cu 26,27 Pt−Ru, 28,29 Pt−Rh, 30,31 Pt−Pd, 32,33 Pt−Ag, 34 and Pt−Au. 35,36 Among Pt-based nanoalloys, Au−Pt bimetallic NPs have attracted much interest due to their inimitable catalytic activity through several reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Microporous and mesoporous materials have very high surface areas occurring from their regular open frameworks with a narrow pore size distribution. These materials can be used as hosts in the template synthesis, providing a confined space for controlled intrapore inclusion chemistry including metals 1 and carbons. 2,3 Hydrocarbon polymer replicas were also reported in such porous materials.…”
mentioning
confidence: 99%